Characterizing the Pathogenic, Genomic, and Chemical Traits of Aspergillus fischeri, a Close Relative of the Major Human Fungal Pathogen Aspergillus fumigatus - Matthew E. Mead (American Society for Microbiology, 2019)
ABSTRACT Aspergillus fischeri is closely related to Aspergillus fumigatus, the major cause of invasive mold infections. Even though A. fischeri is commonly found in diverse environments, including hospitals, it rarely causes invasive disease. Why A. fischeri causes less human disease than A. fumigatus is unclear. A comparison of A. fischeri and A. fumigatus for pathogenic, genomic, and secondary metabolic traits revealed multiple differences in pathogenesis-related phenotypes. We observed that A. fischeri NRRL 181 is less virulent than A. fumigatus strain CEA10 in multiple animal models of disease, grows slower in low-oxygen environments, and is more sensitive to oxidative stress. Strikingly, the observed differences for some traits are of the same order of magnitude as those previously reported between A. fumigatus strains. In contrast, similar to what has previously been reported, the two species exhibit high genomic similarity; ∼90% of the A. fumigatus proteome is conserved in A. fischeri, including 48/49 genes known to be involved in A. fumigatus virulence. However, only 10/33 A. fumigatus biosynthetic gene clusters (BGCs) likely involved in secondary metabolite production are conserved in A. fischeri and only 13/48 A. fischeri BGCs are conserved in A. fumigatus. Detailed chemical characterization of A. fischeri cultures grown on multiple substrates identified multiple secondary metabolites, including two new compounds and one never before isolated as a natural product. Additionally, an A. fischeri deletion mutant of laeA, a master regulator of secondary metabolism, produced fewer secondary metabolites and in lower quantities, suggesting that regulation of secondary metabolism is at least partially conserved. These results suggest that the nonpathogenic A. fischeri possesses many of the genes important for A. fumigatus pathogenicity but is divergent with respect to its ability to thrive under host-relevant conditions and its secondary metabolism. IMPORTANCE Aspergillus fumigatus is the primary cause of aspergillosis, a devastating ensemble of diseases associated with severe morbidity and mortality worldwide. A. fischeri is a close relative of A. fumigatus but is not generally observed to cause human disease. To gain insights into the underlying causes of this remarkable difference in pathogenicity, we compared two representative strains (one from each species) for a range of pathogenesis-relevant biological and chemical characteristics. We found that disease progression in multiple A. fischeri mouse models was slower and caused less mortality than A. fumigatus. Remarkably, the observed differences between A. fischeri and A. fumigatus strains examined here closely resembled those previously described for two commonly studied A. fumigatus strains, AF293 and CEA10. A. fischeri and A. fumigatus exhibited different growth profiles when placed in a range of stress-inducing conditions encountered during infection, such as low levels of oxygen and the presence of chemicals that induce the production of reactive oxygen species. We also found that the vast majority of A. fumigatus genes known to be involved in virulence are conserved in A. fischeri, whereas the two species differ significantly in their secondary metabolic pathways. These similarities and differences that we report here are the first step toward understanding the evolutionary origin of a major fungal pathogen.